الوجود الفلسطیني في لبنان وانعكاسات الازمة الفلسطینیة على الوضع اللبناني: الوجود الفلسطیني في لبنان وانعكاسات الازمة الفلسطینیة على الوضع اللبناني (Journal of the College of Education for Women, 2019)
Abstract:The Palestinian existence in Lebanan is regard as active Arab powersin political system in Lebanan. This existence arises exactly in Lebanan on 5 /June / 1967. The Palestinians distributed from south to north, from Bayrouthto Al-Bquaa, also they lived in Camps like (Tal Al-Zater), (Aen Al-hlwa, Mya –Mya) and so on.The armed Palestinian resistance breakout from these camps inLebanan against Israel, Lebanon rejected this conflict to avoid anyconfrontation with Israel which have big military and high ability in differentaspects in addition security of Lebanan did not connected with security ofArab states in other side the civil war which break out in Lebanon impact uponPalestinians in turn the Palestine crisis impact upon internal setting inLebanan. There is a specific power intervened in Lebanon and Palestine inorder to achieve the (way map) or new Middle East